Effectiveness of Training Programme on Nurses’ Wound Care Competencies after One Year of Implementation - Thi Dung, Phan; Duc Chinh, Nguyen; Phúc Khánh, Pham; Notter, Joy; My Hanh, Bui (The Thai Journal of Surgery, 2017)
This study aims to review the impacts of the nursing training programme on the knowlege, skills and attitude among nurses working in seven clinical departments at Viet Duc University Hospital one year after the interventional programme has been conducted. It was carried out in 2014 and 2015 with a sample size of 145 nurses. The data collection tool included a wound care observation checklist to measure two indicators - the mean score and effects of training on wound care competencies. Data was analysed with SPSS 18.0. The study results showed that the posttraining rate of nurses with adequate practice competencies increased from the pre-training survey (p < 0.001). The effectiveness indicators relating to the competencies of identification, planning, plan implementation and evaluation were 31.9%; 43.3%; 71.3% and 28.3% (p < 0.001). Wound care training programme based on nursing competencies standards has proved to be effective.